Toxicity effect of Diuron on gill tissue structure and the tissue residue of blood cockles Tegillarca granosa - Mohamat Yusuff, Ferdaus; Mohamed Ibrahim, Dhilshad Shereen; Mukhtar, Aqilah; Md Joni, Amirul Azuan; Mohd Kusin, Faradiella; Mohamed, Khairul Nizam; Zulkeflee, Zufarzaana; Ash’aari, Zulfa Hanan; Zulkifli, Syaizwan Zahmir; Ismail, Ahmad; Arshad, Aziz (Elsevier, 2021)
This study aimed to identify the toxicity effect of Diuron on Tegillarca granosa by determining accumulation in the soft tissues and alteration on the gill tissue structure. Wild stocks T. granosa were grouped to identify the initial Diuron concentration and 48-h exposure in different concentrations (0, 1, 2, 3, and 4 mg·L-1). The Diuron in tissue was extracted using an established procedure and identified using High-Performance Liquid Chromatography (HPLC). Gills were analysed for histopathological study; tissue structure was classified and scored using a developed scoring system. Diuron concentration in the soft tissue of exposed T. granosa was in the range 1.27-8.09 mg·kg-1, w/w and not proportionately increase along with the exposure concentration. The mean index values of the gill histopathology ranged from 5.25-7.67 and classified as moderate to severe. Gills characteristics and T. granosa protective behaviour potentially limit Diuron accumulation in the soft tissue.